CNT fibres - yarns between the extremes. Issue 1752 (2015) - Gspann, Thurid S.; Montinaro, Nicola; Windle, Alan H.
Abstract: The carbon nanotube community swims in the sea of superlatives. Researchers expect mechanical performance to achieve two extremes, an ultrastrong fibre taking us into space, and a superlubricant saving energy otherwise lost as heat. We examine CNT fibres in the light of traditional yarn science and present an interpretation of properties which combines aspects of these two extremes of performance.